VIRGIANID BRACHIOPODS OF THE MICHIGAN BASIN, AND ITS IMPLICATIONS FOR POST-EXTINCTION DIVERSIFICATION OF THE SILURIAN PENTAMERIDE FAUNA IN LAURENTIA (Rivista italiana di Paleontologia e Stratigrafia, 2019)
Three virgianid genera are present in the Michigan Basin. The oldest, Virgiana mayvillensis Savage from the Mayville Dolomite, is upper Rhuddanian in age and coeval with the same species on Anticosti Island in eastern Canada. “Virgiana” major Savage, 1916, from the uppermost Lime Island (uppermost Rhuddanian), has an incipient cruralium supported anteriorly by a low median ridge, for which Virgianoides gen. nov. is proposed in this study. Platymerella in the Elwood  Formation (uppermost Rhuddanian) was the most southerly virgianid occurrence in the American mid-continent. The early evolution of the Brevilamnulella-Viridita-Virgiana lineage was represented by the early-middle Rhuddanian fossil record of Anticosti Island. Available fossil data indicate that the Virgiana invasion into intracratonic basins did not begin until late Rhuddanian time, represented by the excellent record of V. mayvillensis in the Michigan Basin, and V. decussata in the Hudson Bay and Williston basins. Despite its late arrival, virgianids thrived for a somewhat longer geological time in the Michigan Basin, represented by Virgianoides and Platymerella in the latest Rhuddanian, when virgianids largely became extinct in other basins of Laurentia.